Fiqh Sosial as a Conceptual Framework for Pesantren-Based Community Empowerment: Insights from Kiai Sahal Mahfudh - Siswanto Siswanto; Muh Luthfi Hakim; Syamsuddin Asrofi; Muhammad Sirril Wafa (Santri: Journal of Pesantren and Fiqh Sosial, 2026)
Fiqh Sosial, developed by Kiai Sahal Mahfudh, is a paradigm of Islamic legal thought that integrates the normative values of Sharīʿah with social realities. It positions fiqh not only as a body of legal doctrines but also as an instrument of community empowerment oriented toward public welfare (maṣlaḥah). This study analyzes the pesantren-based community empowerment model developed by Kiai Sahal Mahfudh, drawing on Jim Ife’s theory of community empowerment. It uses a descriptive-qualitative method with a library research approach. The analysis draws on Jim Ife’s theory, which emphasizes participation, capacity building, community-based development, and social transformation. The findings demonstrate that the model is implemented through productive zakat management, human resource capacity strengthening, continuous community assistance, and the establishment of various pesantren-based social, economic, educational, and health institutions. Analysis through Jim Ife’s framework shows that the model aligns with the principles of community development, particularly community participation, capacity enhancement, social capital development, expanded access to resources, and community self-reliance. Kiai Sahal Mahfudh’s Social Fiqh is a pesantren-based community empowerment model that integrates the social-humanistic empowerment paradigm with Islamic values and the maqāṣid al-sharīʿah.